ปัจจัยที่สัมพันธ์กับภาวะซึมเศร้าของมารดาวัยรุ่นหลังคลอด - จันทร์ศรี, สุนีรัตน์; นิธิพงศ์, วิมลพรรณ; เรืองรอง, บุษยนาฎ (Journal of The Royal Thai Army Nurses, 2017)
งานวิจัยแบบศึกษาย้อนหลังนี้มีวัตถุประสงค์เพื่อศึกษาภาวะซึมเศร้าของมารดาวัยรุ่นหลังคลอด และปัจจัยที่สัมพันธ์กับภาวะซึมเศร้า กลุ่มตัวอย่างเป็นเอกสารบันทึกข้อมูลทุติยภูมิจากแบบสัมภาษณ์ และแบบประเมินภาวะซึมเศร้าของมารดาวัยรุ่นหลังคลอด ที่อายุต่ำกว่า 20 ปี จำนวน 278 คน โดยนำข้อมูลทุติยภูมิที่ได้ วิเคราะห์ด้วยสถิติ ค่าเฉลี่ย ร้อยละ ค่าทดสอบไคสแควร์ ผลการวิจัยพบว่า มารดาวัยรุ่นหลังคลอดมีภาวะซึมเศร้าร้อยละ 6.8 ปัจจัยที่สัมพันธ์กับภาวะซึมเศร้าของมารดาวัยรุ่นหลังคลอดอย่างมีนัยสำคัญทางสถิติคือมารดาวัยรุ่นที่ตั้งครรภ์แรก (X2 = 17.60, p<0.05) และความไม่พร้อมของการตั้งครรภ์ (X2=6.57,p<0.05) ผลการศึกษานี้สามารถนำไปใช้ในการพัฒนาคุณภาพการพยาบาล ด้านการช่วยเหลือ ส่งเสริม และป้องกันภาวะซึมเศร้าในมารดาวัยรุ่นตั้งแต่ระยะฝากครรภ์ครั้งแรก และติดตามจนถึงหลังคลอด โดยคัดกรองภาวะซึมเศร้าในมารดาวัยรุ่นตั้งครรภ์ทุกราย ให้ความใส่ใจเป็นพิเศษในมารดาวัยรุ่นที่ตั้งครรภ์แรก และไม่พร้อมในการตั้งครรภ์ ให้คำปรึกษาช่วยเหลือร่วมกับสหสาขาวิชาชีพ และสร้างเครือข่ายในการดูแลร่วมกับชุมชนอย่างต่อเนื่อง The Factors related to Postpartum Depression in Teenage Mothers The purposes of this retrospective study were to determine postpartum depression in teenage mothers and the factors related to depression among them. The samples were secondary data from case recorded through interview and depression questionnaire approached to 278 postpartum mothers who aged below 20 years old. The data were then analyzed for fnding percentage, mean, and Chi-Square text. The study results revealed that 6.8% of these teenage mothers had postpartum depression. The factors related to depression among them were teenage primigravidarum (X2 = 17.6,p<0.05). and pregnancy without readiness (X2 = 6.57, p<0.05). This study fndings can be used as guideline to effciently develop nursing quality in preventing and supporting postpartum depression in teenage mothers at the beginning of antenatal care including following until postpartum period. In this regard screening depression in every teenage mother should be provided especially in those who are primigravudarum without readiness. Moreover there should be multidisciplinary collaboration in counseling and establish network of care within community continuously.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">